Ansiedade infantil: um olhar para os atrasos no desenvolvimento escolar em crianças dos anos iniciais do Ensino Fundamental - Santos, Geovanna Lopes dos (Universidade Federal do Tocantins, 2023)
This study discusses the theme Childhood Anxiety: a look at delays in school development of children in the early years of Elementary School. Anxiety has been affecting more and more people, including children, delaying their development and, as a consequence, their school performance. This research main objective is to look for evidences of how anxiety disorder can affect the child’s school development. It was found reasons that can trigger certain anxious symptoms in children and influence child development negatively. A humanized and affectionate treatment by teacher to the child is necessary, as well as a school qualified staff. It should also be emphasized the importance of communication between teachers and parents, in order to discuss methods to obtain a child significant performance.